In situ loading amorphous CoSx on N-doped g-C3N4 through light assisted synthesis for enhanced photocatalytic hydrogen generation. (30th April 2023) - Deng, Puhui; Xi, Chuanjun; Chen, Ning; Shi, Hongpeng; Zhang, Linping; Hou, Yu
Abstract: Loading co-catalysts are an effective strategy to break the confinement of bulk carbon nitride in photocatalysis. Employing this strategy, N-doped g-C3 N4 decorated with CoSx was successfully prepared through a photochemical synthesis route. The optimum hydrogen evolution performance of N-CN-CoSx -4 was 1757 μmol g −1 h −1 under visible light irradiation. Superior interfacial carrier transfer properties and improved light absorption of N-CN-CoSx -4 could elucidate its better photocatalytic activity. This research offers a reference for the construction of high-efficiency, stable and low-priced photocatalysts. Graphical abstract: CoSx fabricated N-doped g-C3 N4 was successfully prepared using thermal condensation and photodeposition. The composition material achieves excellent hydrogen evolution performance which benefits from the improvement of optical absorption and accelerated interfacial charge transfer. Image 1 Highlights: CoSx was fabricated on N-doped g-C3 N4 by photodeposition. N-doping and loading CoSx promote the photocatalytic H2 evolution activity of g-C3 N4 . N-doping improves the light absorption and introducing CoSx accelerates the interfacial electron transfer.